The Effect of Training and Use of Information Technology on the Quality of the Financial Statement of Village-Owned Enterprises - Mutia Maulita Anggraeni; Sahmin Noholo; Amir Lukum (Magister Akuntansi, Universitas Atma Jaya Makassar, 2023)
This research aimed to figure out the effect of training and the use of information technology on the quality of the financial statement of village-owned enterprises. This research employed a quantitative descriptive method where the data source of this research was primary data obtained directly from respondents through questionnaires distributed to village-owned enterprises administrators and village officials in Tabongo Subdistrict, Gorontalo Regency. Besides, the total population amounted to 54 people, with a total sample was 30 village-owned enterprises administrators determined by using purposive sampling. The findings denoted that partially, the training variable (X1) had a positive and significant effect on the quality of the financial statement of village-owned enterprises (Y), the use of information technology variable (X2) had no significant effect on the quality of the financial statement of village-owned enterprises (Y). Meanwhile, simultaneously, the training (X1) and the use of information technology (X2) variables had a positive and significant effect on the quality of the financial statement of village-owned enterprises (Y).